Employment and Retirement Following a Late Career Job Loss - Sewin Chan; Ann Huff Stevens (Rutgers University, Department of Economics, 1999)
The frequency of job loss among workers in late career has risen disproportionately in recent years. The effects of job loss on these workers are potentially severe: their earnings capacity, savings, and retirement expectations are likely to be dramatically affected and they may take substantially longer to be re-employed. However, despite these reasons for heightened concern, relatively little is known about the economic consequences of late career job loss among recent cohorts of workers. This paper presents findings from an ongoing research project using the Health and Retirement Study that focuses on the economic impacts of late career job loss on employment and retirement patterns, as well as on earnings and assets.
Keywords: J26; J64; 330; aging; employment; job loss; retirement